Interactive Animation-Based Learning Video Media for Computer Systems Material - Dian Rahadian; Rani Mardiani; Rivan Syahrul Falah (Universitas Pendidikan Ganesha, 2026)
The survey results and distribution of the needs questionnaire indicate that Computer Systems learning in class X of the Computer and Network Engineering expertise program is still dominated by conventional methods, leading students to be passive and experience difficulties understanding concepts. This study aims to analyze learning needs and develop and test the feasibility of interactive animated video media as an innovative solution. This research is development research using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 25 students. Data were collected through validation questionnaires from material and media experts, as well as student response questionnaires, and analyzed using quantitative descriptive techniques. The results of the study show that the developed media were assigned to a feasible category by material and media experts and received very high student response in the large-group trial stage. These findings indicate that the developed animated video media is feasible and effective for improving student understanding and have implications for strengthening technology-based learning that is more interactive and innovative.